Aboriginal and Treaty Rights in Canada : Essays on Law, Equality, and Respect for Difference. - Asch, Michael (UBC Press, 1997)
In the last two decades there has been positive change in how the Canadian legal system defines Aboriginal and treaty rights. Yet even after the recognition of those rights in the Constitution Act of 1982, the legacy of British values and institutions as well as colonial doctrine still shape how the legal system identifies and interprets Aboriginal and treaty rights. What results is a systematic bias in the legal system that places Indigenous peoples at a distinct disadvantage. The eight essays in Aboriginal and Treaty Rights in Canada focus on redressing this bias. All of them apply contemporary knowledge of historical events as well as current legal and cultural theory in an attempt to level the playing field. The book highlights rich historical information that previous scholars may have overlooked. Of particular note are data relevant to better understanding the political and legal relations established by treaty and the Royal Proclamation of 1763. Other essays include discussion of such legal matters as the definition of Aboriginal rights and the privileging of written over oral testimony in litigation. The collection also includes an essay that, by means of ethnographic and historical data, raises concerns respecting how the law might be distorted even further if we are not careful in assuring that what is defined as Indigenous today is detached from its own traditions and divorced from contemporary issues. In sum, Aboriginal and Treaty Rights in Canada shows that changes in the way in which these rights are conceptualized and interpreted are urgently needed. This book then offers concrete proposals regarding substantive, processual, and conceptual matters that together provide the means to put change into practice.